2023
DOI: 10.1371/journal.ppat.1011506
|View full text |Cite
|
Sign up to set email alerts
|

NRF2 activators inhibit influenza A virus replication by interfering with nucleo-cytoplasmic export of viral RNPs in an NRF2-independent manner

Abstract: In addition to antioxidative and anti-inflammatory properties, activators of the cytoprotective nuclear factor erythroid-2-like-2 (NRF2) signaling pathway have antiviral effects, but the underlying antiviral mechanisms are incompletely understood. We evaluated the ability of the NRF2 activators 4-octyl itaconate (4OI), bardoxolone methyl (BARD), sulforaphane (SFN), and the inhibitor of exportin-1 (XPO1)-mediated nuclear export selinexor (SEL) to interfere with influenza virus A/Puerto Rico/8/1934 (H1N1) infect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Unexpectedly, we also showed that 4-OI induced a cellular antiviral program that potently inhibited a broad range of viruses including SARS-CoV-2, Herpes Simplex virus 1 and 2 (HSV-1/2), Vaccinia Virus, and Zika Virus, and that without promoting an inflammatory state 34 . This antiviral action was also observed by two other groups, reporting that 4-OI reduced influenza A virus replication by directly targeting the nuclear export protein CRM1 35 , 36 .…”
Section: Introductionsupporting
confidence: 76%
“…Unexpectedly, we also showed that 4-OI induced a cellular antiviral program that potently inhibited a broad range of viruses including SARS-CoV-2, Herpes Simplex virus 1 and 2 (HSV-1/2), Vaccinia Virus, and Zika Virus, and that without promoting an inflammatory state 34 . This antiviral action was also observed by two other groups, reporting that 4-OI reduced influenza A virus replication by directly targeting the nuclear export protein CRM1 35 , 36 .…”
Section: Introductionsupporting
confidence: 76%
“…It is unlikely that activation of Nrf2 is the sole mechanism for the observed antiviral effect of itaconic acid, as the potent Nrf2 activator dimethyl itaconate (DI) ( 28 ) failed to restrict viral replication of IAV in a similar magnitude as 4-OI ( 4 ). In fact, a recent study suggested the antiviral properties of 4-OI to be Nrf2 independent but to interfere with IAV RNPs instead via interaction with CRM1 ( 29 ). Indeed, other antiviral mechanisms have been proposed for the activity of itaconate derivatives against influenza viruses such as targeting of the nuclear export of IAV vRNPs ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of Nrf2 pathway to antiviral effects of flavonoids and various herbal phenolic compounds remains to be elucidated in detail. Recent findings support the role of various Nrf2 activators in inhibiting influenza virus replication [39]. Catechin flavonoids have been shown to inhibit TGEV-induced ROS and cytopathic effect [40].…”
Section: Discussionmentioning
confidence: 66%